Phenolic Polymers Based Composite Materials - Jawaid, Mohammad; Asim, Mohammad (Composites Science and Technology, 2021)
This book contains recent research on phenolic resin and its composite materials. The book covers all types of wood composites, natural fibres and synthetic fibres reinforced composites. It discusses various properties of phenolic composites and presents comparative study with other polymer composites for prospective applications. The chapters in the book present an up-to-date information on the subject area of polymer and composite-based information by prominent researchers in academia and industry as well as government/private research laboratories across the world. The book serves as a holistic reference source for university and college faculties, professionals, postdoctoral research fellows, undergraduate/graduate students, and research and science officers working in the area of polymer science, non-forest products utilization, natural fibres and biomass materials